Potensi Antioksidan Menggunakan Metode DPPH Ekstrak Beras Hitam (Oryza Sativa L Indica) dan Penghambatan Tirosinase (Jurnal Health Sains, 2021)
Black Rice (Oryza sativa L. Indica) is a rice commonly used to improve health. Black rice has a physical shape similar to rice in general, but the surface of this rice is blackish purple. The study aimed to test the antioxidant activity and tyrosinase inhibitors in black rice extract. The study was conducted from February 2019 to August 2019. Using experimental methods. Black rice is extracted by the maceration method using 96% solvent ethanol, then several tests are performed using spectrophotometry. Observed parameters include phytochemical test results, antioxidant activity, and tyrosinase inhibition activity. Tests of antioxidant activity and inhibition of tyrosinase were observed from IC50 (inhibitor concentration) values. The results of phytochemical analysis showed that black rice extract contains flavonoids, tannins, and triterpenoids. The antioxidant activity test is performed using the DPPH (2,2-diphenyl-1-picrihydracil) method which has very strong antioxidant activity with an IC value of < 10 ppm. Brown rice extract has inhibition of tyrosinase. The conclusion that can be from this study is that black rice extract phytochemicalally contains flavonoids, tannins, and triterpenoids that are included in antioxidant compounds.